Corals in high diversity reefs resist human impact. (November 2016) - Ferrigno, F.; Bianchi, C.N.; Lasagna, R.; Morri, C.; Russo, G.F.; Sandulli, R.
Abstract: Coral reefs are amongst the most diverse ecosystems in the biosphere. However, they also represent one of the most threatened marine systems. Apart from global change, especially fishing and tourism affect coral reefs either with mechanical damage or with increase of pollution and sedimentation. Recently, the increase of disturbances has induced extensive changes in community structure and composition of coral reefs. Well-balanced and rich communities can better resist disturbances and show a more rapid recovery, compared to less biodiverse systems. This study assesses the status of coral reefs subjected to several anthropogenic pressures, using a modified version of Coral Condition Index (CCI) that takes into account all Acropora and Pocillopora growth forms and considers a further category of coral damage: the presence of disease. The investigations were carried out at Bangka Island (North Sulawesi, Indonesia), where some of the most flourishing reefs in the country are present. The CCI takes into account the extent of different damages on coral colonies, particularly of the genera Acropora and Pocillopora, being among the most widespread bioconstructors of local coral reefs and very sensitive to anthropogenic disturbances. The aim of the present work is to test whether the CCI is a reliable index in different coral reefs, and to evaluate if highly biodiverse reefs show a better resistance to several human stressors. Data showed high values of CCI (0.9 on average) at all the investigated sites and at the two depths (3 and 9 m) for each site, with the most abundant category represented by "healthy coral colonies". These data indicate a reasonably good health status of the reef in the study area (CCI > 0.8). The presence of different types of human pressure in the study area was evaluated through the use of metric proxies. Results do not seem to show any significant influence of such human activities on reef coral status, as shown by the low values of correlation between CCI values and the distances of the study sites from the three main sources of stress (Villages, Resorts and Other). Moreover, the present data seem to confirm that highly biodiverse and well-structured assemblages can resist disturbances more efficiently and that human pressure in the study area is sustainable. Compared to fishing activities, the impact of Scuba diving on coral reef is lower, resulting more sustainable and ecologically non-destructive. CCI summarizes many kinds of information and can be applicable in various areas with different pressures. It is a useful tool that might help to assist and guide management decisions towards alternative development models.